The Society and its contribution to Ireland: past, present and future - Daly, Mary E. (Statistical and Social Inquiry Society of Ireland, 1998)
'The one hundred and fiftieth anniversary of the founding of the Statistical and Social Inquiry Society of Ireland is a time to take stock, to remember the Society?s past'. - [p.1 (orig. p.33)] '...It is important to note the changes that have taken place within the Society over the past 150 years and the elements of continuity. There is a continuing emphasis on practical matters, as opposed to subjects which are of primarily theoretical interest. Indeed the Society?s activities could be summarised in one brief phrase: The Condition of Ireland. As Roy Geary noted in his introduction to the centenary history, `it is fascinating to observe how in each generation the studies under Society auspices reflected the public interests of the time?. Anybody who seeks a time capsule of the major social and economic topics during a particular decade should consult the Journal. If they do so they will discover that some topics recur repeatedly, most significantly demography. However it is also important to recognise the changes that have taken place'. - [p.3 (orig. p.35)]
Read before the Society, 13 November 1997
Keywords: Statistical and Social Inquiry Society of Ireland - History; Royal Dublin Society - History; 314.15